1994
DOI: 10.1139/v94-206
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of DL-penicillamine by chromium(VI). Kinetics of formation of the thioester intermediate

Abstract: , 1637 (1994). The kinetics of formation of the thioester involved as an intermediate in the reaction between chromium(V1) and or.-penicillamine in aqueous media (pH = 1-8) containing different buffers (acetate, citrate, and phosphate) has been studied by monitoring the disappearance of chromium(V1) at 370 nm and application of the initial-rates method. The initial rate is directly proportional to the initial concentrations of both oxidant and reductant, and the rate vs. pH plots show bell-shaped profiles. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 11 publications
(20 reference statements)
3
16
0
Order By: Relevance
“…The mechanism proposed for the formation of CrOO 2+ , Equations (6)-(9), can explain the finding that the yield of the intermediate CrOO 2+ in the reactions of chromate with three different thiols follows the sequence: DL-penicillamine > L-cysteine > glutathione [8]. This sequence is the opposite of that corresponding to the yield of the intermediates HRSCrO À 3 in the same reactions, and it is coincident with the sequence DL-penicillamine (k 2 ¼ 9:62Â 10 À3 s À1 Þ > L-cysteine ðk 2 ¼ 1:66 Â 10 À3 s À1 Þ > glutathione ðk 2 ¼ 0:80 Â 10 À3 s À1 Þ, corresponding to the rate constants for the redox decay of those intermediates (k 2 in Scheme 1) measured under the same experimental conditions (acetate buffer, ionic strength 0.20 M, pH 5.60, 25.0°C) [22].…”
Section: Formation Of the Intermediate Croo 2+mentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism proposed for the formation of CrOO 2+ , Equations (6)-(9), can explain the finding that the yield of the intermediate CrOO 2+ in the reactions of chromate with three different thiols follows the sequence: DL-penicillamine > L-cysteine > glutathione [8]. This sequence is the opposite of that corresponding to the yield of the intermediates HRSCrO À 3 in the same reactions, and it is coincident with the sequence DL-penicillamine (k 2 ¼ 9:62Â 10 À3 s À1 Þ > L-cysteine ðk 2 ¼ 1:66 Â 10 À3 s À1 Þ > glutathione ðk 2 ¼ 0:80 Â 10 À3 s À1 Þ, corresponding to the rate constants for the redox decay of those intermediates (k 2 in Scheme 1) measured under the same experimental conditions (acetate buffer, ionic strength 0.20 M, pH 5.60, 25.0°C) [22].…”
Section: Formation Of the Intermediate Croo 2+mentioning
confidence: 99%
“…spectra obtained by difference spectroscopy for the intermediate CrOO 2+ in the reactions of chromate ion with two sulfhydryl-containing amino acids, L-cysteine (present work) and DL-penicillamine [8], are compared with those corresponding to the u.v. spectrum of authenticated CrOO 2+ obtained by ordinary spectroscopy in Table 2.…”
Section: Nature Of the Intermediate Detected By Uv Difference Spectmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of our effort was directed to the oxidations by Cr(VI) of thiolic type substrates such as thiols, thioacids, thioethers [5][6][7][8][9]. Same area studies by other groups are also found in the literature [5,[10][11][12] and some general patterns are now well established. Among them there is a first and often fast step in which one Cr(VI) and one or more thio compound molecules form a condensation intermediate (adduct).…”
Section: Introductionmentioning
confidence: 99%
“…Although investigations on the interactions of Cr(VI) with thiol compounds have been extensively reported [9,10,[18][19][20][21], no electrochemical and spectroscopic studies dealing with the fotocatalytic effect of UV light on the interaction of Cr(VI) with cysteine have appeared in the literature. Therefore, in the present work, the role of UV irradiation in the reduction of Cr(VI) with cysteine has been investigated with cyclic voltammetry and electronic spectroscopy techniques.…”
Section: Introductionmentioning
confidence: 99%